mRNA Vaccines Enhance Neutralizing Immunity against SARS-CoV-2 Variants in Convalescent and ChAdOx1-Primed Subjects - Dorit Fabricius; Carolin Ludwig; Judith Scholz; Immanuel Rode; Chrysanthi Tsamadou; Eva-Maria Jacobsen; Martina Winkelmann; Aline Grempels; Ramin Lotfi; Aleš Janda; Sixten Körper; Guido Adler; et al. (Vaccines, 2021)
To identify the most efficient methods of immunological protection against SARS-CoV-2, including the currently most widespread variants of concern (VOCs)—B.1.1.7, B.1.351 and P.1—a simultaneous side-by-side-comparison of available vaccination regimes is required. In this observational cohort study, we compared immunological responses in 144 individuals vaccinated with the mRNA vaccines BNT162b2 or mRNA-1273 and the vector vaccine ChAdOx1-nCoV-19, either alone, in combination, or in the context of COVID-19-convalescence. Unvaccinated COVID-19-convalescent subjects served as a reference. We found that cellular and serological immune responses, including neutralizing capacity against VOCs, were significantly stronger with mRNA vaccines as compared with COVID-19-convalescent individuals or vaccinated individuals receiving the vector vaccine ChAdOx1-nCoV-19. Booster immunizations with mRNA vaccines triggered strong and broadly neutralizing antibody and IFN-γ responses in 100% of vaccinated individuals investigated. This effect was particularly strong in COVID-19-convalescent and ChAdOx1-nCoV-19-primed individuals, who were characterized by comparably moderate cellular and neutralizing antibody responses before mRNA vaccine booster. Heterologous vaccination regimes and convalescent booster regimes using mRNA vaccines may allow enhanced protection against SARS-CoV-2, including current VOCs. Furthermore, such regimes may facilitate rapid (re-)qualification of convalescent plasma donors with high titers of broadly neutralizing antibodies.